Decompressive hemicraniectomy following malignant middle cerebral artery infarctions: a mixed methods exploration of carer experience and level of burden. (1st June 2013) - McKenna, A.; Wilson, F. C.; Caldwell, S.; Curran, D.; Nagaria, J.; Convery, F.; Storey, L.
Abstract : Purpose : This study explores the experiences and sense of burden of family carers of survivors of malignant middle cerebral artery infarctions who had undergone decompressive hemicraniectomy. To date, there have been no studies examining carer outcomes among this unique population. This study, taken alongside an already published study of survivor outcomes, provides a more holistic picture with regard to sequelae within the sample. Method : Six family carers completed the Sense of Competence Questionnaire and the Hospital Anxiety and Depression Scale. These results were compared with existing normative data. Carers also consented to a semi-structured interview. Interview data were examined using thematic content analysis. Consistent with the mixed methods design, quantitative and qualitative findings were integrated for further analysis. Results : While carers experienced many losses, their overall sense of burden was not outside 'Average' limits, nor did they experience clinically significant symptoms of depression. All carers identified methods of coping with the demands of caregiving. These included intrapersonal, interpersonal and practical strategies. All carers apart from one were able to identify areas of post-traumatic growth. Conclusion : Carers will benefit from information, support and care. In addition, problem solving skills are essential in managing the myriad difficulties that arise in the aftermath of stroke.